2005
DOI: 10.1016/j.orthres.2004.10.001
|View full text |Cite
|
Sign up to set email alerts
|

In vivo three‐dimensional wrist motion analysis using magnetic resonance imaging and volume‐based registration

Abstract: This study represents a new attempt to non-invasively analyze three-dimensional motions of the wrist in vivo.A volume-based registration method using magnetic resonance imaging (MRI) was developed to avoid radiation exposure. The primary aim was to evaluate the accuracy of volume-based registration and compare it with surface-based registration. The secondary aim was to evaluate contributions of the scaphoid and lunate to global wrist motion during flexionxxtension motion (FEM), radio-ulnar deviation (RUD) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 18 publications
5
60
0
1
Order By: Relevance
“…2 While translation does occur in the wrist joint (Patterson et al, 1998;Valero-Cuevas and Small, 1997), it has been shown to be small (Kaufmann et al, 2005;Kaufmann et al, 2006), indicating that FE and RUD are well approximated as being purely rotational DOFs. Many studies have shown that FE occurs slightly more proximal than RUD (Andrews and Youm, 1979;Brumbaugh et al, 1982;Goto et al, 2005;Kaufmann et al, 2005;Kaufmann et al, 2006;Leonard et al, 2005;Neu et al, 2001;Sommer and Miller, 1980). Therefore, the wrist joint can be described kinematically as a universal joint with nonintersecting axes (Fig.…”
Section: Kinematic Datamentioning
confidence: 99%
“…2 While translation does occur in the wrist joint (Patterson et al, 1998;Valero-Cuevas and Small, 1997), it has been shown to be small (Kaufmann et al, 2005;Kaufmann et al, 2006), indicating that FE and RUD are well approximated as being purely rotational DOFs. Many studies have shown that FE occurs slightly more proximal than RUD (Andrews and Youm, 1979;Brumbaugh et al, 1982;Goto et al, 2005;Kaufmann et al, 2005;Kaufmann et al, 2006;Leonard et al, 2005;Neu et al, 2001;Sommer and Miller, 1980). Therefore, the wrist joint can be described kinematically as a universal joint with nonintersecting axes (Fig.…”
Section: Kinematic Datamentioning
confidence: 99%
“…Segmentation was defined as extracting vertebrae required for processing [1][2][3][4]. Contours of individual vertebrae in the neutral position were semi-automatically segmented from 3D MRI using intensity thresholding techniques.…”
Section: Segmentation Of the Vertebraementioning
confidence: 99%
“…Kinematic variables were measured by automatically superimposing segmented 3D MRI of the vertebrae in the neutral position over images for each position using this method of registration [1][2][3][4]. The correlation coefficient was used as a method of measuring similarity of voxel values for registration.…”
Section: Volume Registrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of carpal kinematics in vitro (Kobayashi et al, 1997;Patterson et al, 1998;Werner et al, 2004) and in vivo (Crisco et al, 2003;Moojen et al, 2002;Neu et al, 2001;Sun et al, 2000;Wolfe et al, 2000;Goto et al, 2005) provide useful descriptive data, but do not provide predictions of performance. Computational wrist modeling, including rigid body spring models (RBSM) (Genda and Horii, 2000;Iwasaki et al, 1998;Manal et al, 2002;Schuind et al, 1995) for kinematics and finite element (FE) studies (Carrigan et al, 2003) for stress distributions under static loads have constrained the wrist to neutral or functional (grip maneuver) postures.…”
Section: Introductionmentioning
confidence: 99%